Imaging breast cancer response during neoadjuvant systemic therapy. Issue 5 (October 2005) - Beresford, Mark; Padhani, Anwar R; Goh, Vicky; Makris, Andreas
Neoadjuvant systemic therapy is used to enable breast-conserving surgery in patients with large primary operable breast cancers. It is important to be able to accurately assess response to systemic therapy, both to assist the surgeon and for prognostic purposes. Moreover, a proportion of women will fail to respond to treatment and would potentially benefit from either a change in therapy or earlier surgery rather than continuing completion of the planned course of treatment. Conventional techniques of assessing response (clinical examination, x-ray mammography and breast ultrasound) rely on changes in tumor size, which are often delayed and do not always correlate with pathologic response. This review examines the evidence for functional imaging techniques including scintimammography, functional computed tomography, dynamic magnetic resonance imaging, spectroscopy and positron emission tomography. These techniques measure changes in tumor vasculature, metabolism or proliferation and may prove to be earlier and more sensitive measures of response to systemic therapy, thus enabling tailoring of an individual's treatment.